Livelihood strategies of coastal fishermen on Pangkor Island using a modified livelihood strategies determinants framework / Ho Siew Neo - Ho , Siew Neo (2019)
Sustainable development of a nation involves efficient, appropriate and sustainable use of various resources. However, there is no single sustainable livelihood framework which can be generalized. Therefore, this study explores the factors affecting Pangkor Island coastal fishermen decision on choice of livelihood strategies. An exploratory sequential mixed method approach was applied whereby eight findings were gathered and reorganized into eight factors to be tested in quantitative phase. Livelihood Strategies Framework (LSF) was developed, treating the eight factors as independent variables and two livelihood strategies, i.e. livelihood intensification and livelihood diversification, as dependent variables. An open-ended interview questions were utilized as guided questions in qualitative data collection phase, while a survey questionnaire was employed in quantitative phase to gather necessary data. Quantitative data were validated using Exploratory Factor Analysis (EFA) and were analysed using Structural Equation Model (SEM) and Pearson correlation analysis. A total of 15 interviews were carried out in the qualitative phase while a total of 165 responses were gathered in the quantitative data collection phase. This study revealed two important findings: (1) education level, level of income versus expenses, trend of output, coping strategies adopted, risk, and fishermen view of sustainable income are significant factors affecting fishermen choice of livelihood intensification strategies, while (2) education level, level of income versus expenses, trend of output, and willingness to learn are significant factors affecting their choice of livelihood diversification strategies. These findings are useful for the authorities in the future planning for the social and economic welfare development of coastal fishermen in Malaysia and subsequently affects the Malaysia’s fiscal planning.